EFEKTIFITAS MODEL PEMBELAJARAN PROBLEM BASED LEARNING DENGAN MEDIA PUZZLE TERHADAP HASIL BELAJAR IPAS MATERI METAMORFOSIS KELAS III SDN WATUPECAH - Retno Wulandari; Ifa Seftia Rakhma Widiyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The learning outcomes of metamorphosis of grade III at SDN Watupecah, Kragan District, which have not yet met expectations, are the focus of the study. This study aims to evaluate how well the PBL model using puzzle media improving learning outcomes about metamorposis for grade III students at SDN watupecah in the 2025 academis year. This type of research is quantitative ond uses a one-group pretest-posttest design. The results showed that the avarage pretest score wa 55,8 while the posttest score reached 79,4. After conducting the t test, it was obtained with N=20. The calculated t was 4,782404, while the t table with db=N-1=20-1=19 and a significance level of 0,05 was 2,093. Because the calculated t value>t table, the accepted H₀ and Ha indicate that the problem based learning model is effective in learning outcomes of science science metamorphosis material for grade III SDN Watupecah, Kragan District. The application of problem based learning models can create a more interesting, dynamic, and efficient learning atmosphere to support the student learning process.